2013
DOI: 10.1037/a0031650
|View full text |Cite
|
Sign up to set email alerts
|

The development and implications of peer emotional support for student service members/veterans and civilian college students.

Abstract: Student service members/veterans represent a growing population on college campuses. Despite this growth, scholarly investigations into their health- and adjustment-related issues are almost nonexistent. The limited research that is available suggests that student service members/veterans may have trouble connecting with their civilian counterparts and be at risk for social isolation. The present study compared the development and implications of emotional support from peers among 199 student service members/v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 78 publications
3
89
1
Order By: Relevance
“…Here, there is an obligation not only to connect veterans with other veterans, but also to create the opportunity for civilians and veterans to engage one another in meaningful, nonjudgmental discussions about the significance of war and the impact of war's violence. Our findings echo existing research about the potential value of familial and social support beyond just the veteran community (Romero et al, 2015;Whiteman, Barry, Mroczek, & MacDermid Wadsworth, 2013). Counseling psychologists and mental health professionals can work to cultivate this support by participating in or organizing public educational events, humanities-focused engagements, volunteer opportunities, and other creative community venues that are focused on learning about war and the military experience, with a particular focus on the moral concerns that can arise for, and sometimes haunt, combat veterans.…”
Section: Discussionmentioning
confidence: 40%
“…Here, there is an obligation not only to connect veterans with other veterans, but also to create the opportunity for civilians and veterans to engage one another in meaningful, nonjudgmental discussions about the significance of war and the impact of war's violence. Our findings echo existing research about the potential value of familial and social support beyond just the veteran community (Romero et al, 2015;Whiteman, Barry, Mroczek, & MacDermid Wadsworth, 2013). Counseling psychologists and mental health professionals can work to cultivate this support by participating in or organizing public educational events, humanities-focused engagements, volunteer opportunities, and other creative community venues that are focused on learning about war and the military experience, with a particular focus on the moral concerns that can arise for, and sometimes haunt, combat veterans.…”
Section: Discussionmentioning
confidence: 40%
“…Military experience is an additional level of identity military-connected students must navigate during their transition to college (DiRamio & Jarvis, 2011). Many identity factors included in this study have been explored in literature related to military-connected students' transition experiences, including sex and gender (Baechtold & De Sawal, 2009;Demers, 2013;DiRamio & Jarvis, 2011;DiRamio, Jarvis, Iverson, Seher & Anderson, 2015), first-generation student status (Durdella & Kim, 2012), and family (having a spouse, partner and/or dependent children) (Whiteman et al, 2013). Although the role of ethnicity for military-connected students has not been highly researched, almost 40% of military-connected students identify as non-White Beyond social identity characteristics, extant literature has explored the role of deployment (DiRamio et al, 2008;Rumann & Hamrick, 2010) and service-related injury or disability (Kraus & Rattray, 2013;Schiavone & Gentry, 2014).…”
Section: Cornerstonesmentioning
confidence: 99%
“…Currently, universities stress the need to develop structures to provide transition, social support, emotional connection and financial advice (Burnett & Segoria, 2009;Selber & Chavkin, 2014;Summerlot, Green, & Parker, 2009;Whiteman, Barry, Mroczek, & MacDermid Wadsworth, 2013). A recent survey showed that 76% of universities had a military affairs program to manage these mechanisms, 60% expected these to be long term arrangements, and most had set long-term goals to expand programs and provide extensive marketing to the military student population (Cook & Kim, 2009).…”
Section: Discussion/conclusionmentioning
confidence: 99%